The impact of the organisational system on the implementation of an Employee Value Proposition (EVP) at Air Traffic and Navigation Services (ATNS) - Sparks, Chanel (My University, 2018)
ABSTRACT An employee value proposition (EVP) is a significant enabler of an organisations strategy. A well-defined EVP provides organisations with a competitive advantage in the continuous global war for talent. This allows organisations to attract and retain talent. The transport sector - particularly aviation - is a critical component of the economy, affecting development and the welfare of the entire population – both as an enabler of economic wellbeing and its beneficiaries. When transport systems efficiently provide for the needs of society and enable sustainable opportunities, they positively impact on the well-being of the country. According to the Air Traffic and Navigation Services (ATNS) website, the state-owned entity provides air traffic, navigation, training and associated services within South Africa and a large part of the Southern Indian and Atlantic Ocean, comprising approximately ten (10) percent of the worlds airspace. EVP is a key enabler for success at ATNS as an organisation. Even though there are processes and systems in place, ATNS, like any other organisation, has faced key human resource challenges. To identify key issues related to challenges of the people aspect at ATNS, this research study was conducted. This was done to determine what the EVP of the organisation is and what contributing factors within the organisational system impact the EVP. The problem statement for this study has been defined as “What is the impact of the organisational system on the implementation of an Employee Value Proposition at ATNS”? The literature review that was conducted, identified the following three independent variables that are linked to the organisational system: leadership effectiveness; policies, processes and systems as well as employee involvement. Dependent variables identified for EVP were employer brand, attraction and retention, employee motivation and employee engagement. Applied social research has been used for this research study as opposed to basic social research. Applied social research uses scientific methodology to develop information to help solve an immediate, yet usually persistent societal problem. A quantitative research methodology was used in conducting this research. Random sampling was used to identify the sample from the ATNS population (workforce). From the 1200 employees at ATNS, 200 were selected and the response rate was hundred (100) percent. Questionnaires were used to gather data and were assigned numerical values. The research results strongly indicate that employees at ATNS are aware of what an EVP is, and that it influences their choice to work for the company. The results further indicate that the employees of ATNS are of aware of the elements within the organisational system, and that an organisational system is a key enabler of EVP at the organisation. The effectiveness of these elements within the organisational system impacts the implementation of an EVP at ATNS. Leadership effectiveness as an organisational system element and talent retention & attraction as a variable within EVP, is key to the successful implementation of EVP at ATNS. The research results can assist management to understand what the key drivers of an EVP are within ATNS. Management is now presented with an opportunity to determine the level of leadership effectiveness within the organisation. The success of this intervention in the future may be determined by doing a survey on employee’s perception pre and post the implementation of this programme. Management may further link these results to the elements within an EVP and how it impacts on retention, engagement levels and motivation. Ethics was also taken into consideration in the research study, where participants were informed of the voluntary nature of their participation and the confidentiality of the results. The research results indicate that the EVP variable most impacted by leadership effectiveness is attraction and retention. The research study focused on ATNS and may not be generalised for the entire transport industry. The results could, however, provide insight and understanding for EVP within the aviation sector. Due to the fact that the research study was of a quantitative nature, insights and participants reactions to questions could not be determined.
Keywords: Airports Company. Airports -- South Africa. Business -- Vocational guidance.